PLANT GROWTH-PROMOTING BACTERIA ASSOCIATED WITH NITROGEN FERTILIZATION IN Eucalyptus urophylla INCREASE GROWTH - Santos, R. K. A.; Ferreira, J. S.; Paula, R. C. de [UNESP]; Rodrigues, V. A.; Silva, V. A. M. da; Santos, J. da S. (Centro Federal Educacao Tecnologica Rio Grande Norte, 2021)
The objective of this study was to evaluate plant growth-promoting bacteria in eucalyptus, associated with different levels of ammonium sulfate, to know the benefits to initial plant growth, determining which nitrogen level and bacterial isolate is the most effective. Five bacterial isolates and one control without inoculation were used, besides 4 levels of ammonium sulfate, 0, 20, 40 and 60 mg dm(-3) N, in a factorial scheme and randomized block design, set in a 20-L pot, with Eucalyptus urophylla clone AEC144. Height, diameter, dry matter, leaf area, Spad index, Ntotal and photosynthesis were evaluated. The isolates UESBJMR32E and UESBJNR32E promote initial growth in eucalyptus plants associated with intermediate doses of ammonium sulfate.
Keywords: Eucalyptus; rhizobacteria; ammonium sulfate